Pengaruh E-Commerce dan QRIS Terhadap Pendapatan UMKM Berbasis E-digital di Kota Jambi - Anggraeni , Lidya; Anggraini, Dessy (ILTIZAM Journal of Shariah Economics Research, 2025)
This study aims to analyze the influence of e-commerce and QRIS usage on the income of digital-based Micro, Small, and Medium Enterprises (MSMEs) in Jambi City. Using a descriptive quantitative approach, the research involved 150 respondents randomly selected from the population of digital-based MSMEs in Jambi City. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that, both partially and simultaneously, e-commerce and QRIS have no significant effect on the income of digital-based MSMEs. The coefficient of determination (R²) reveals that only 1.4% of the variation in MSME income can be explained by these two variables. These findings suggest that the adoption of e-commerce and QRIS among MSMEs in Jambi City is not yet optimal, with major challenges including low digital literacy, limited technological access, and restricted utilization of features. The study highlights the need for intensive training and improved digital infrastructure to support MSME digital transformation, enabling them to maximize the potential of e-commerce and QRIS in increasing income.